A class of extracellular vesicles from breast cancer cells activates VEGF receptors and tumour angiogenesis - Qiyu Feng (Nature Portfolio, 2017)
Extracellular vesicles (EVs) contain VEGF and can contribute to tumour angiogenesis, although the mechanism remains unclear. Here, the authors find that a form of VEGF (VEGF90K) resistant to Bevacizumab but sensitive to HSP90 inhibitors, associates with EVs through its interaction with Hsp90.